Manajemen Kesehatan Larva Kerapu Cantang (Epinephelus fuscoguttatus x Epinephelus lanceolatus) di BBRBLPP Gondol - Muh. Sulaiman Dadiono; Maheno Sri Widodo; Emyliana Listiowati; Baruna Kusuma (Samakia : Jurnal Ilmu Perikanan, 2022)
Larval health management is a serious problem faced by hatcheries of cantang grouper (E. fuscoguttatus x E. lanceolatus) in order to avoid large financial losses due to larval death. Health Management of cantang grouper larvae includes larval rearing, larval feed management, larval disease control and water quality management. Primary data collection methods are active participation, observation and direct interviews. Secondary data collection by means of literature study. Cantang grouper larvae were reared in the hatchery to control the temperature and condition of the larvae. The ponds were sterilized with 3-5 ppm chlorine in the morning and 3-5 ppm thiosulfate in the afternoon. Then rinsed so that no residual chlorine. Larvae were reared from day 1 to day 45. Larvae were fed from 2 days old with Nannochloropsis occulata. Rotifers were given when the larvae were 2-3 days old with a density of 5 individuals/ml. Artemia was given when the larvae were 18 days old until the age of 40 days. Pellets are given when the larvae are 8-10 days old with a pellet size of level 1. The pellet size continues to increase according to the larval mouth opening until harvest. The disease that attacks the larvae is Viral Nervous Necrosis. The characteristics of larvae infected with VNN are reduced appetite, weak movement, larvae float on the surface and lie on the bottom of the pond. The bacteria that often attack larvae is Vibrio alginolyticus. Vibrio alginolyticus can be treated using drugs from natural ingredients. The temperature in the larval pond is 28-30oC and the salinity is 34-35 ppt. This temperature and salinity are still quite good for grouper larvae to live.